Development of Students' Creative Thinking Skills by Organizing Music Culture Lessons Based on STEAM Education - Najimovich, Rahmonkulov Abdujabbor (International Journal on Integrated Education, 2023)
This article focuses on the theoretical and practical processes of forming the ability to use the acquired knowledge, skills and abilities in life on the basis of expanding the scope of students' creative thinking, growth and development of creative abilities by organizing musical culture classes based on STEAM education.